ARCHITECTURAL AND ARTISTIC ORGANIZATION OF FACADES OF MODERN BUILDINGS IN HISTORICAL CITIES OF UZBEKISTAN (AS AN EXAMPLE OF THE CITY OF SAMARKAND) - J.X. Kadirov; S.M.Suvankulov (Scholar Express Journals, 2024)
The article is aimed at researching the principles of architectural and artistic organization of the facades of new buildings in the historical part of Samarkand, developing the facades of buildings that reflect traditionality and modernity in our architecture, and analyzing and harmonizing the principles of the built ones.
Keywords: The article is aimed at researching the principles of architectural and artistic organization of the facades of new buildings in the historical part of Samarkand, developing the facades of buildings that reflect traditionality and modernity in our architecture, and analyzing and harmonizing the principles of the built ones.; artistic means; Residence; Historical city